PAST AND PRESENT. IMAGINE UTOPIAS FEMINISTS FROM THE SOUTH - ciriza, alejandra (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
This work recovers utopian elements in discourses born from feminist practices in Abya Yala. It starts from a delimitation of the notion of utopia that puts its historical roots in dialogue with forms of exercise of the utopian function in the present. Some feminist experiences situated and linked to the defense of common goods are presented as utopias of return of the past, as a retracing of the marks of colonization. Hence the question about the ties between past and present, about the secret rendezvous that summons More in the current exercise of the utopian function. Feminists in Abya Yala, defenders of their natural and corporeal territories, bring the past to the present in their struggles under the assumption that there is continuity between human beings and nature. They point out the impossibility of reproducing life under the logic of capitalist accumulation and the advance on nature inaugurated with colonial plunder, while projecting other forms of social organization. More had done something similar in the 16th century. He denounced the impossibility of reproducing life in the England of his time and imagined an island of future where England’s conflicts would be solved. Imagination launched him towards the future and towards the placeless place that was America for the Europeans of his time. If the answer separates them, a similar way of considering the effective conditions of existence brings them closer in the form of utopian imagination.